FUNCTIONAL OUTCOME OF TENNIS ELBOW (LATERAL EPICONDYLITIS) TREATED BY LOCAL INJECTION OF PLATELET RICH PLASMA - Jiwani, Rahil; Mehta, Satish; Kadam, Abhijit (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to evaluate the efficacy of local injection of platelet rich plasma in management of patients with tennis elbow who failed to respond to conservative management. Methods: This was a prospective and cohort study in which 80 patients with lateral epicondylitis (Tennis elbow) were included on the basis of a predefined inclusion and exclusion criteria. Demographic details were noted. Patients were treated by local injection of autologous platelet rich plasma. Patients were followed up for 6 months. Relief of pain as well as functional improvement was assessed by patient-rated tennis elbow evaluation (PRTEE) score. SSPS 21.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: Out of 80 studied cases, there were 36 (45%) males and 44 (55%) females with a M: F ratio of 1:1.22. The mean age of male (42.77±9.95 years) as well as female (41.06±9.56 years) was found to be comparable. Nineteen (23.75%) patients were involved in plumbing, 16 (20%) patients were involved in activities that required forceful use of screwdrivers such as electric work, 8 (10%) patients were involved in gardening, and 7 (8.75%) patients were involved in production or laying of bricks. Twelve (15%) patients were professional tennis player. The mean PRTEE score was 74.24±9.74 at the time of presentation. There was significant reduction in PRTEE score during follow-up and at the time of last follow-up visit, PRTEE score was found to be 8.32±2.56. Conclusion: Local injection of autologous platelet rich plasma is effective in managing patients of lateral epicondylitis (Tennis elbow) who fail to respond to conservative management.